Microbiological profile of symptomatic and asymptomatic bacteriuria recovered from female patients with urinary tract infection (Stamford Journal of Microbiology, 2015)
With the previous knowledge on the production of ?-lactamase by the bacterial pathogens causing urinary tract infection, present study further investigated the presence of symptomatic and asymptomatic bacteriuria in female patients admitted into the Delta Medical College with suspected urinary tract infections (UTIs). The manifestation of uropathogens and their responses against locally available antibiotics (amoxicillin, 10 ?g; cephradin, 30 ?g; ciprofloxacin, 5 ?g; cotrimoxazole, 23.8 ?g; gentamicin, 10 ?g; nalidixic acid, 30 ?g) were inquired by means of conventional cultural techniques and double-disc diffusion methods, respectively. Among 110 urine samples collected from the patients with suspected UTI, 34 were found to be culture positive. Symptomatic (64.7%) and asymptomatic (36.3%) bacteriuria were noticed inside the puss cell of the UTI positive cases. Escherichia coli (73.5%) was the dominant bacteria while Klebsiella spp. (26.5%) was also exultant. Around 96% uropathogens were found to be sensitive against imipenem, and 75% against amikacin. E. coli was found to be sensitive against all of the antibiotics used, whereas Klebsiella spp. was found to be 100% resistant against nalidixic acid and cotrimoxazole. DOI: http://dx.doi.org/10.3329/sjm.v3i1.22751 Stamford Journal of Microbiology, Vol.3(1) 2013: 34-37